The Influence of Google Earth Learning Media on Geography Thinking Skills and Student Learning Outcomes - Lukman Hakim; Sri Astutik; Muhammad Asyroful Mujib (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2023)
Interesting media or learning models are needed in realizing geography thinking skills, One of the interesting learning media is Google Earth. The purpose of this study is to examine the influence of Google Earth learning media on geography thinking skills and student learning outcomes. The type of research used is experimental research with Posttest Only Control Group Design. The results of this study were divided into two, namely data on students' critical thinking skills and data on student learning outcomes. The results showed that geography's thinking skills showed the value of Asymp. Sig. (2-tailed) is 0.003, while student learning outcomes show Asymp scores. Sig. (2-tailed) of 0.000. From these data, it can be decided that Google Earth learning media has a significant effect on geography thinking skills and student learning outcomes.